Bowel preparation for colorectal surgery: with and without mannitol - Askarpour, Shahnam; Peyvasteh, Mehran; Dastyar, Ali-Asghar; Javaherizadeh, Hazhir (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction : In our country due to some limitations, mannitol is widely used for bowel preparation. Bowel preparation with mannitol has several side effects. Aim: To compare complication of mechanical bowel preparation with and without mannitol. Material and methods : This case control study was carried out in Imam Khomeini and Abuzar children’s hospitals. Sixty cases of patients who underwent colorectal surgery were included in this study. Pull-through, colostomy closure, and anorectoplasty were the surgical procedures. Subjects were randomly placed in the case or control group. Infection, electrolyte disturbances, fever, and leukocytosis were recorded. Multivariate analysis was done using PRISM. Odds ratio was calculate with CI = 95%. Results: Fourteen boys and 16 girls were included in group I. Ten boys and 20 girls were included in group II. Twenty colostomies, 6 pull-throughs, and 4 anorectoplasties were performed in group I. Twenty-one colostomies, 5 pull-throughs, and 4 anorectoplasties were done in group II. Mean age of the patients was 2.63 ±1.9 and 2.66 ±1.68 for group I and group II respectively (p = 0.262). Following bowel preparation with mannitol, 14 patients had mild fever with mean body temperature of 38.1°C. Three subjects had postsurgical fever within 48 h of surgery. In group II, postoperative fever was found in 2 subjects. Conclusions : Hypernatremia, hypokalemia, and leukocytosis were more common in patients who underwent bowel preparation with mannitol.